Prospective analysis of risk factors and angiographic profile in women with coronary artery disease –A hospital based study - Singh, Subhasish; Pradhan, Rashmita (Asian Journal of Medical Sciences, 2021)
Background: In order to facilitate diagnosis and timely intervention, it is essential to understand the presentation pattern of cardiac symptoms, and distribution of risk factors in women with Coronary Artery Disease (CAD). However, limited data is available regarding the salient features of CAD in women like distribution of risk factors and anatomical extent. Aims and Objective: The purpose of the present study was to determine the clinical and risk factor profile of women admitted with CAD and to analyze their angiographic findings in relation to the clinical presentation and risk factors in a tertiary care referral center of eastern India. Materials and Methods: In this study we prospectively analysed risk factors and angiographic patterns of 140 consecutive female patients who underwent coronary angiography for suspected CAD over a period of 2 years. Results: CAD most commonly affected females of age group >60yrs with higher incidence among postmenopausal as compared to premenopausal women. Unstable angina was the commonest presentation among patients with normal coronaries as well as obstructive CAD.A substantial percentage of women presenting with anginal pain were angiographically normal. Hypertension was the most common associated risk factor followed by diabetes, elevated total cholesterol, high LDL & low HDL. Most common coronary angiography finding was single vessel disease. On analysis, diabetes mellitus, elevated cholesterol, elevated LDL & triglycerides were most commonly associated with triple vessel disease. Conclusion: The incidence of CAD in females increased with age. Single vessel disease was the commonest presentation with Left Anterior Descending Artery, the most frequently involved vessel.